Valvular heart disease in pregnancy: maternal and fetal outcome - Akhter, N; Rahman, F; Salman, M; Anam, K; Begum, N; Naher, S; Fatema, N; Hasan, Z; Rashid, MA; Benerjee, SK (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):436-440 The abstract of this article is available on the PubMed website